ENTERPRISE RISK MANAGEMENT PADA CLOUD COMPUTING - Samudra Dipa Legawa (Universitas Muhammadiyah Tangerang, 2017)
Advances in information technology have changed the way of processing information who used to be a mainframe to personal computers to the web-based computing.Today, many organizations are seriously considering adopting cloud computing technology,Cloud computing is the combined use of computer technology in a network with the development of Internet-based (cloud) which has the function to run a program or application via a computer - a computer connected at the same time. However, the application of cloud computing itself led to various risksKata kunci : teknologi informasi, cloud computing, manajemen resiko